Structural controllability of high order dynamic multi-agent systems - Partovi, Alireza; Lin, Hai; Ji, Zhijian (2010 IEEE Conference on Robotics, Automation and Mechatronics, 2010)
Recently, the controllability problem of multi-agent systems is significantly explored; however, the majority of studies have been focused on the classical controllability approaches. This paper investigates the necessary and sufficient conditions of structural controllability for high order dynamic multi-agent systems. We consider a group of agents in a leader-follower framework under a fixed topology structure. It is assumed that, the agents interconnection is a weighted graph with freely chosen weights and each agent has a high order controllable canonical dynamic. Under this setup we show that the structural controllability of such a network is directly determined by agent interconnection. It is shown that a set of weights can be found which make the entire network controllable if and only if the graph is connected. Finally, we present a numerical example and simulation to illustrate the results.